1952
DOI: 10.1590/s0074-02761952000100024
|View full text |Cite
|
Sign up to set email alerts
|

Notas de Ixodologia: II - uma nova espécie do gênero Amblyomma e uma nova espécie do gênero Ixodes (Acari Ixodidae)

Abstract: A new tick, Amblyomma parkeri, n. sp., is described as a parasite of Coendu sp. from S. Paulo, Brazil. Female holotype, nymph and larva are described (Figs. 2 e 3). The n. sp. differs completly from Koch's species Amblyomma longirostre, the common parasite of the Erethizotidae. Standard data for measures of the female dorsal scutum ixodidae are proposed as follows (fig. 1): PA = Antero-posterior; PB = Postero-basal; PM = Postero-median; TT = Transversal; OO = Inter-ocular; OT= Occulo-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In the present study, we present the first description of the male of A. parkeri and provide morphological evidence to support the original description of A. parkeri (Fonseca and Aragão 1952) and subsequent works that considered it a valid taxon (Aragão and Fonseca 1961;Camicas et al 1998;Guimarães et al 2001;Guglielmone et al 2003;Barker and Murrell 2004). This evidence was supported by molecular analyses of portions of the 16S rRNA and 12S rRNA mitochondrial genes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In the present study, we present the first description of the male of A. parkeri and provide morphological evidence to support the original description of A. parkeri (Fonseca and Aragão 1952) and subsequent works that considered it a valid taxon (Aragão and Fonseca 1961;Camicas et al 1998;Guimarães et al 2001;Guglielmone et al 2003;Barker and Murrell 2004). This evidence was supported by molecular analyses of portions of the 16S rRNA and 12S rRNA mitochondrial genes.…”
Section: Discussionsupporting
confidence: 84%
“…Before the present study, reports of A. parkeri were known only from the type specimens described by Fonseca and Aragão (1952). However, reexamination of all available specimens of A. longirostre and A. geayi in tick collections showed that these 2 species have occasionally been misidentified.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…More than 35 species of Ixodes have been reported in the Neotropical zoogeographic region, but this genus is one of the most difÞcult to distinguish taxonomically and there are still several doubtful species throughout the world (Clifford et al 1973). Fonseca and Aragão (1952) described a tick collected from opossums in Brazil, which they called Ixodes didelphidis Fonseca & Aragão, a species closely related to Ixodes (Ixodes) loricatus Neumann. This later species is a common ectoparasite of opossums in central-southern Brazil, and has been reported from Mexico to Argentina (Cooley and Kohls 1945).…”
mentioning
confidence: 99%